Bans on Cellphone Use While Driving and Traffic Fatalities in the United States - Zhu, Motao (Epidemiology, 2021)
As of January 2020, 18 of 50 US states comprehensively banned almost all handheld cellphone use while driving, 3 states and the District of Columbia banned calling and texting, 27 states banned texting on a handheld cellphone, and 2 states had no general cellphone ban for all drivers. However, it remains unknown whether these bans were associated with fewer traffic deaths and whether comprehensive handheld bans are more effective than isolated calling or texting bans. We evaluated whether cellphone bans were associated with fewer driver, non-driver, and total fatalities nationally. METHODS: We conducted a longitudinal panel analysis of traffic fatality rates by state, year, and quarter. Population-based rate ratios and 95% CIs were estimated comparing state–quarters with and without cellphone bans. RESULTS: From 1999 through 2016, 616,289 persons including 344,003 drivers died in passenger vehicle crashes in the United States. Relative to no ban, comprehensive handheld bans were associated with lower driver fatality rates (adjusted rate ratio aRR = 0.93, 95% CI = 0.90, 0.97) but not for non-driver fatalities (aRR = 1.01, 95% CI = 0.95, 1.07) or total fatalities (aRR = 0.98, 95% CI = 0.94, 1.01). We found no differences in driver fatalities for calling-only bans (aRR = 1.00, 95% CI = 0.97, 1.03), texting-only bans (aRR = 1.02, 95% CI = 0.99, 1.05), texting plus phone-manipulating bans (aRR = 0.99, 95% CI = 0.93, 1.04), or calling and texting bans (aRR = 0.98, 95% CI = 0.88, 1.09). CONCLUSIONS: Comprehensive handheld bans were associated with fewer driver fatalities.